Implementasi Etika Bisnis Islam pada Kualitas Produk, Pelayanan, dan Administrasi Halva Bakery Tangerang - Didi Suardi; Herman Syahroni; Martavevi Azwar; Iti Septi; Aisyah Defy R. Simatupang; Oom Komariyah; Nur Jamaludin (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This study examines the implementation of Islamic business ethics in the business practices of Halva Bakery, Villa Rizky Ilhami, Kelapa Dua, Tangerang, Banten. The research focuses on seven indicators of Islamic business ethics: honesty in measurement, product quality, avoiding excessive oaths, generosity in service, administrative order, price transparency, and maintaining trust. This study uses a qualitative field research approach, with data collected through interviews, observation, and documentation. The findings indicate that Halva Bakery has not fully implemented Islamic business ethics. Three aspects require improvement: product quality, employee service ethics, and administrative effectiveness. In terms of product quality, several consumers found that some bread products had a hard texture, less attractive form, and inconsistent packaging. In service practice, some employees were perceived as not fully demonstrating polite communication, neat appearance, and friendly treatment toward all customers. In addition, administrative constraints, especially payment system disruptions, caused inconvenience for customers. This study contributes to the development of Islamic business ethics studies in small-scale food enterprises by showing that ethical business implementation must integrate product quality, service behavior, and administrative reliability. Strengthening these aspects is essential to build consumer trust and ensure that business practices align with Islamic values